Brugada syndrome disease phenotype explained in apparently benign sodium channel mutations - Malcolm Hoshi (2018)
Background-Brugada syndrome (BrS) is an arrhythmogenic disorder that has been linked to mutations in SCN5A, the gene encoding for the pore-forming a-subunit of the cardiac sodium channel. Typically, BrS mutations in SCN5A result in a reduction of sodium current with some mutations even exhibiting a dominant-negative effect on wild-type (WT) channels, thus leading to an even more prominent decrease in current amplitudes. However, there is also a category of apparently benign (atypical) BrS SCN5A mutations that in vitro demonstrates only minor biophysical defects. It is therefore not clear how these mutations produce a BrS phenotype. We hypothesized that similar to dominant-negative mutations, atypical mutations could lead to a reduction in sodium currents when coexpressed with WT to mimic the heterozygous patient genotype. Methods and Results-WT and atypical BrS mutations were coexpressed in Human Embryonic Kidney-293 cells, showing a reduction in sodium current densities similar to typical BrS mutations. Importantly, this reduction in sodium current was also seen when the atypical mutations were expressed in rat or human cardiomyocytes. This decrease in current density was the result of reduced surface expression of both mutant and WT channels. Conclusions-Taken together, we have shown how apparently benign SCN5A BrS mutations can lead to the ECG abnormalities seen in patients with BrS through an induced defect that is only present when the mutations are coexpressed with WT channels. Our work has implications for risk management and stratification for some SCN5A-implicated BrS patients. © 2014 American Heart Association, Inc.